2022
DOI: 10.1038/s41598-022-20736-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota shift in layer pullets fed on black soldier fly larvae-based feeds towards enhancing healthy gut microbial community

Abstract: Globally, most gut microbiota-related studies have focused on broilers due to their diverse microbial communities compared to that of layer chicken. However, in Africa few studies have been undertaken despite the increasing benefits to the poultry industry. The utilization of Insect-Based diets to improve the gastrointestinal function and gut health in poultry is increasingly gaining global attention. Here, we evaluated the potential roles of commercial black soldier fly larvae-based feeds (BSFLF) in reshaping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Since diets incorporating BSFL meals have been shown to modify pathways associated with bile acid metabolism, it could conceivably be hypothesized that such a diet may benefit enterocyte lipid digestion and gut physiology. These benefits are in accordance with previous studies showing that a BSFL diet can broadly improve gut health in chickens and fish [15,44]; however, a few attempts have been made to elucidate the relation between the profiles of microbial metabolites and gut physiology. Therefore, the interactions among microbial metabolites, enterocyte metabolism, and gut homeostasis should be investigated for an in-depth understanding of the dietary benefits of BSFL meals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since diets incorporating BSFL meals have been shown to modify pathways associated with bile acid metabolism, it could conceivably be hypothesized that such a diet may benefit enterocyte lipid digestion and gut physiology. These benefits are in accordance with previous studies showing that a BSFL diet can broadly improve gut health in chickens and fish [15,44]; however, a few attempts have been made to elucidate the relation between the profiles of microbial metabolites and gut physiology. Therefore, the interactions among microbial metabolites, enterocyte metabolism, and gut homeostasis should be investigated for an in-depth understanding of the dietary benefits of BSFL meals.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, feeding with a low level of BSFL (10%) to layers leads to an increase in caecal microbial diversities [ 14 ]. Ndotono et al conclude a similar finding that the gut microbial diversity of laying hens fed with BSFL meal as a complete replacement of fishmeal (10%) is higher than that of laying hens fed with control diets [ 15 ]. Furthermore, Biasato et al indicated that a 5% level of BSFL meal inclusion is more beneficial to the gut health of broilers than the addition of 10% and 15% BSFL meal in terms of changes in gut microorganisms and intestinal mucin production [ 16 ].…”
Section: Introductionmentioning
confidence: 92%
“…In agreement with our observations associated with diets containing high amounts of BSFLM on the cecal bacterial diversity of male broiler chickens, similar studies examining the effect of complete replacement of SBM or fish meal with BSFLM in Lohmann Brown Classic laying hen [ 21 ] and ISA brown layer chick [ 34 ] diets, have also reported increased in bacterial richness and Shannon’s diversity index, together with significant changes in beta diversity of gut bacterial communities [ 34 ]. In contrast, for diets with low BSFLM content, Biasato et al showed that replacement of SBM with 15% BSFLM (but not 5% and 10%) was associated with a reduction in Shannon’s diversity in the cecal microbiota of 35-day-old broiler chickens [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, Lactobacillus (12.17−67.01%) constituted one of the predominant genera in the ileum across different age groups. Ndotono et al [37] and Ngunjiri et al [23] found that Lactobacillus species belonging to the family Lactobacillaceae were the predominant bacteria in the chicken ileum in their respective studies. This bacterial family comprises beneficial commensals that have been extensively studied in both the human and animal food and medical industries [18].…”
Section: Discussionmentioning
confidence: 98%